Pregnancies with Platelet Count Lower Than 70000 Platelets/μl - Semih Mun; Fatma Horasan Çelimli; Tolga Mızrak; Mesut Polat; Ümit Naykı; Cüneyt Eftal Taner (Medical Network, 2006)
OBJECTIVE: In this study, pregnancies complicated with thrombocytopenia platelet count lower than 70000 platelets/μl were ev aluated. STUDY DESIGN: Twenty two pregnancies with platelet count lower than 70000 platelets/μl were ev aluated according to age, platelet count, vital signs, gestational age at the diagnosis, need of transfusion, birth weight, newborn's thrombocytopenia, type of delivery, gestational age, dose and duration of cortisone use and additional maternal complications. RESULTS: Mean age of the group was 26.0 (range 18-35) years. Four cases had the diagnosis of Immune Thrombocytopenic Purpura (ITP). Within the ITP group one pregnancy ended with intrauterine mortal fetus at 16th week of gestation. Four patients had hypertension with thrombocytopenia; two of them had the diagnosis of HELLP Syndrome, two had chronic hypertension. The other 14 patients with thromcocytopenia had no other maternal disease and they were accepted as gestational thrombocytopenia. Among these 14 patients one of the pregnancies ended with intrauterine mortal fetus at 27 weeks of gestation, the others had healthy babies. In the study group four cases, with the diagnosis of ITP necessitated steroid therapy. 60 mg/day steroid therapy was administered. In two cases the therapy lasted for six days till delivery, in the other 2 it lasted in 30 days. Among all patients eight of them needed prophy lactic transfusion before deliveries. Among these 8 patients, one delivered vaginally and 7 delivered by cesarean section. Among all patients two had intrauterine mortal fetus and among the other 20 cases there were 2 preterm deliveries at 33rd and 34th weeks of gestation. Mean gestational age of our study group was 38.5 weeks (range 30-40 weeks). Among 20 pregnancies with healthy fetuses, 11 pregnants underwent cesarean section, 9 delivered vaginally. There was no signif icant bleeding associated with vaginal deliveries or cesarean sections. No inf ants had asphyxia (1st and 5th minutes apgar scores were 7 or more) at birth. Platelet counts were measured for 20 inf ants and there was neither thrombocytopenia nor a complication among these infants. CONCLUSION: If thrombocyte count of a pregnant is not less than 70000/μl and her symptoms are not related with thrombocytopenia then only follow up for platelet counts is sufficient in pregnancy. However if it is less than 70000/μl, treatment of thrombocytopenia and strict follow up of patient is necessary.